THE ANALYSIS ON FICTIONAL FINALISM FAILURES CAUSED BYDUALISM IN T. S. ELIOT'S THE LOVE SONG OF J. ALFRED PRUFROCK(1909) : AN INDIVIDUAL PSYCHOLOGICAL APPROACH - NOVITA, ELLA RATNA (2010)
This research focuses on the exploration of fictional finalism failures that happen to J. Alfred Prufrock, the main character in T. S. Eliot's The Love Song of J. Afred Prufrock. Because of dualism, he suffers from many failures in fulfilling his basic need of perfections about women, love, and marriage in his life as a normal person. The objectives of this research are to analyze the poem based on its structural elements of the poem, to identify the types of fictional finalism failures caused by dualism as shown in T.S. Eliot's The Love Song of J. Alfred Prufrock and to describe how these failures are portrayed in the poem. This research applies a descriptive method. The source of data in this thesis is the book of Robert B.Kaplan entitled Major Poems and Plays of T.S. Eliot. The main data consist of lines, stanzas, and quotations that support this research. To reach the purposes above, the researcher applies the psychological theory of striving for perfection delivered by Alfred Adler, the philosophical theory of dualism by Rene Descartes, and the semiotic theory by Michael Riffaterre. The reason of using these approaches is based on the consideration that Prufrock has difficulties to manage his life. He has broken personality caused by dualism that leads him to further failures to fulfill his need of perfections. The result of the study shows that there were several fictional finalism failures encountered by Prufrock. They were the failure of striving for compensation caused by dualism in personality, the failure of striving for superiority caused by dualism in social status, the failure of aggression drive fulfillment caused by dualism in life cycle, and the failure of masculine protest caused by dualism in sex differentiation. Those failures were described using binary opposition concept and imageries to strengthen the depiction of those failures happening in Prufrock's dramatic monologue.